+0  
 
0
241
2
avatar+262 

sabi92  Jul 12, 2015

Best Answer 

 #1
avatar+26322 
+10

You can factor it as:

 

$$(x-\frac{1}{2})(x-4m+\frac{1}{2})=0$$

 

so  

$$\\ x=\frac{1}{2}\\ or\\x=4m-\frac{1}{2}$$

.

Alan  Jul 12, 2015
Sort: 

2+0 Answers

 #1
avatar+26322 
+10
Best Answer

You can factor it as:

 

$$(x-\frac{1}{2})(x-4m+\frac{1}{2})=0$$

 

so  

$$\\ x=\frac{1}{2}\\ or\\x=4m-\frac{1}{2}$$

.

Alan  Jul 12, 2015
 #2
avatar+90988 
+5

Thanks Alan,

OR

You could solve it by completing the square method

 

$$\\x^2-4xm+(2m-\frac{1}{4})=0\\\\
x^2-4xm\;=\;-(2m-\frac{1}{4})\\\\
x^2-4xm+(2m)^2\;=\;-2m+\frac{1}{4}+(2m)^2\\\\
(x-2m)^2\;=\;-2m+\frac{1}{4}+4m^2\\\\
(x-2m)^2\;=\;4m^2-2m+\frac{1}{4}\\\\
(x-2m)^2\;=\;4(m^2-\frac{m}{2}+\frac{1}{16})\\\\
(x-2m)^2\;=\;4(m-\frac{1}{4})^2\\\\
x-2m\;=\;\pm 2(m-\frac{1}{4})\\\\
x\;=\;2m\pm 2(m-\frac{1}{4})\\\\
x\;=\;2m+ 2m-\frac{1}{2}\qquad or \qquad x\;=\;2m- 2m+\frac{1}{2}\\\\
x\;=\;4m-\frac{1}{2}\qquad or \qquad x\;=\;\frac{1}{2}\\\\$$

Melody  Jul 13, 2015

11 Online Users

avatar
avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details